INSTITUSI KESEHATAN: KAJIAN SARANA DAN PRASARANA PENDUKUNG KESETARAAN GENDER - Eva Gusmira; Badariah Badariah; Wahab Wahab (Kafa`ah: Journal of Gender Studies, 2021)
This research study of facilities and infrastructure supporting gender equality at health institutions aims to see the extent of the availability of facilities and infrastructure to support health institution services, especially hospitals in the city of Jambi and how hospital policies regarding the implementation of government policies relating to gender equality. This research uses a combined research method (Mixed Method Research) with a sequential Explanatory type strategy, with a quantitative data collection design followed by qualitative data. The population in this study is a hospital in the city of Jambi with a sample of 3 hospitals with state hospitals taken by purposive sampling technique. Data collection techniques using observation techniques, questionnaires, interviews and documentation and data validation with triangulation techniques. The data analysis technique used in this study used a mixed method technique. Quantitative data analysis uses a percentage and Likert scale followed by qualitative analysis. This study found that hospitals in the city of Jambi have sufficient status to meet hospital standards with facilities and infrastructure supporting gender equality with a percentage value of 48.73% of the 13 parameters of the facilities and infrastructure studied. These results indicate that the implementation of government policies in supporting gender equality has not yet been realized.